1998
DOI: 10.1212/wnl.51.6.1629
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral sildenafil (Viagra) in men with erectile dysfunction caused by spinal cord injury

Abstract: Oral sildenafil, taken as required (not more than once daily), significantly improves the quality of erections and satisfaction with sex life in men with erectile dysfunction caused by a spinal cord injury between T6 and L5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
8

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 3 publications
3
78
0
8
Order By: Relevance
“…1,2 Either or both psychogenic (nonsomesthetic supraspinally elicited) and reflexive (somesthetic spinally elicited) erections, confirmed by urodynamic and electrophysiologic findings, are necessary for response to sildenafil therapy. 3 In addition, sildenafil due to the positive effect on the quality of a partnership showed long-term compliance compared to invasive treatment such as intracavernosal injection of alprostadil.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Either or both psychogenic (nonsomesthetic supraspinally elicited) and reflexive (somesthetic spinally elicited) erections, confirmed by urodynamic and electrophysiologic findings, are necessary for response to sildenafil therapy. 3 In addition, sildenafil due to the positive effect on the quality of a partnership showed long-term compliance compared to invasive treatment such as intracavernosal injection of alprostadil.…”
Section: Introductionmentioning
confidence: 99%
“…2,[6][7][8]15,16 Such was the case that the monitoring of blood pressure and other side effects was performed in a setting lacking sexual stimuli. Neither the time or the site of the study were suitable for reliable assessments of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…2,[6][7][8][13][14][15][16] In all these studies, sildenafil was reported to have notable efficacy for obtaining and maintaining an erection in patients with SCI. However, in many of these studies, 2,6,7 patients with neurological levels of SCI above T5 were systematically excluded due to the potential risk of autonomic dysreflexia and, especially, of hypotension. Similarly, many of the studies excluded individuals with hypotension (systolic/diastolic blood pressure o90/50 mmHg, respectively).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations